Equação do 1 grau:
- 2 ( x - 1 ) + 2 = 3 ( x - 4 )
me ajudem pfv
Soluções para a tarefa
Respondido por
1
-2(x-1)+2=3(x-4)
-2x+2+2=3x-12
-2x-3x=-12-4
-5x=-16
x=-16/-5
x=3,2
Espero ter ajudado!
-2x+2+2=3x-12
-2x-3x=-12-4
-5x=-16
x=-16/-5
x=3,2
Espero ter ajudado!
Litalucena:
-2 multiplicado por -1 é igual a 2, e não 3
Respondido por
1
-2(x-1)+2=3(x-4)
-2x+4=3x-12
-5x= -16
x=-16/-5
x=3,2
-2x+4=3x-12
-5x= -16
x=-16/-5
x=3,2
Perguntas interessantes
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás